2017
DOI: 10.1002/job.2185
|View full text |Cite
|
Sign up to set email alerts
|

An organizational ethic of care and employee involvement in sustainability‐related behaviors: A social identity perspective

Abstract: We expand on the emergent research of an ethic of care (EoC) to theorize why and how an organizational EoC fosters employee involvement in sustainability-related behaviors at work. Across two studies, we explore the socio-psychological mechanisms that link an EoC and involvement in sustainability-related behaviors. The results of Study 1, in which we applied an experimental design, indicate that an EoC is significantly related, through employees' affective reaction towards organizational sustainability, to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(169 citation statements)
references
References 127 publications
12
155
0
2
Order By: Relevance
“…After that, expert mining was conducted to finalize the enablers of HRD for sustainability. Further, our study supports the literature how enablers of quality of work life are playing a significant role for long term sustainability of organization (Nguyen et al, 2017;Carmeli et al, 2017;Delmas and Pekovic, 2018). Third, we have developed a structural model by ISM and future the interrelationships tested using TISM from data collected from the Indian power sector.…”
Section: Implication and Contribution For Theorysupporting
confidence: 79%
“…After that, expert mining was conducted to finalize the enablers of HRD for sustainability. Further, our study supports the literature how enablers of quality of work life are playing a significant role for long term sustainability of organization (Nguyen et al, 2017;Carmeli et al, 2017;Delmas and Pekovic, 2018). Third, we have developed a structural model by ISM and future the interrelationships tested using TISM from data collected from the Indian power sector.…”
Section: Implication and Contribution For Theorysupporting
confidence: 79%
“…They propose that the care enacted through discursive practices and everyday working relationships increases organizational members’ feelings of support and connection. Carmeli, Brammer, Gomes, and Tarba (2017, p. 1380) also apply Gilligan’s work at the organizational level of analysis to empirically examine ‘why and how an organizational EoC fosters employee involvement in sustainability‐related behaviors at work’. They found that organizations that exhibited care towards their employees foster higher levels of employee satisfaction and involvement in sustainability‐related activities.…”
Section: Ethics Of Care and Crisis Managementmentioning
confidence: 99%
“…Therefore it is a prerequisite that the leaders act as role models for their employees [60]. Furthermore, organizational ethics of care [61] and commitment towards the environment [62,63] can also encourage employees to include more sustainability-oriented behaviors at the workplace. Organizational green policies and practices such as green human resource management are also major contributors to sustainable behavior at work [64].…”
Section: Employee Sustainability Behaviormentioning
confidence: 99%